Out of love for my kin aristocratic family life in the lands of the Loire, 1000 - 1200 - Livingstone, Amy 1961- (History/Medieval, 2010)
Introduction : aristocrats and their families -- The lands of the Loire, 1000-1200 -- Aristocratic family life -- Aristocratic family life writ small : the Fréteval, Mondoubleau, and Dives kindred -- Inheritance : diversity and continuity -- Marriage and the disposition of property : a sign of status? -- Marriage : practicalities, ideologies, and affection -- For better, not worse : wives and husbands as partners in family and lordship -- Contestations : asserting and reasserting a place in the family -- Conclusion : out of love for my kin